ANNUAL PERMANENCY OF THE AMERICAN WHITE PELICAN Pelecanus erythrorhynchos IN ENSENADA DE ARIPES, BAJA CALIFORNIA SUR, MEXICO - Mendoza-Salgado, RA; Amador, E; Salinas-Zavala, C; Palacios, E (Ecosistemas y Recursos Agropecuarios, 2014)
This is the first report of the American White Pelican (Pelecanus erythrorhynchos ) residing over a three year and three month period at Ensenada de Aripes, Baja California Sur. The pelicans remained in the study area throughout the year. Some non-breeding individuals stay in the region, suggesting that the adults migrate to their nesting areas